Ways of using digital technologies to increase the efficiency of banking activity in the banking system of Uzbekistan. (Texas Journal of Multidisciplinary Studies, 2023)
Digital banking technologies and their structure and elements in the banking system of the Republic of Uzbekistan are widely covered in this article. The scientific views of foreign and local scientists on banking technologies were studied, analyzed and author's opinions were expressed. Also, the possibilities of introducing digital technologies and their elements in the banking system on a large scale, their advantages and directions for its improvement are proposed